STRATEGI PENDEKATAN KONTEKSTRUAL PADA PEMBELAJARAN DI SEKOLAH DASAR UNTUK MENINGKATKAN PEMAHAMAN SISWA - Lira Adawiyah (Jurnal Salome : Multidisipliner Keilmuan, 2026)
Contextual learning is an approach that links subject matter to real world situations experienced by students. This approach aims to improve students' conceptual understanding and critical thinking skills. This article discusses the implementation of contextual learning strategies in elementary schools and their impact on students' conceptual understanding. Through this method, students are invited to connect the knowledge gained with everyday life thereby increasing their learning motivation and understanding.